Sergio Blanco. Autoficción: una ingeniería del yo. Madrid, Punto de Vista Editores, 2019. 111 pp. - Menestrina, Enzo Matías (Badebec, 2020)
Sergio Blanco. Autoficción: una ingeniería del yo. Madrid, Punto de Vista Editores, 2019. 111 pp.